MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DALAM PERSPEKTIF 5R (RINGKAS, RESIK, RAPI, RAWAT DAN RAJIN) DAN RELEVANSINYA DENGAN NILAI-NILAI ISLAM DI MADRASAH ALIYAH NEGERI 1 PONOROGO - Maya Estiyanti; M. Zainal Arif; Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2021)
Management of educational facilities and infrastructure is very important to support the success of learning in schools. Madrasah Aliyah Negeri 1 Ponorogo is one of the schools that has fulfilled the 5R elements (Concise, Clean, Neat, Careful and Diligent) and existing Islamic values. This study aims to determine the implementation of management of educational facilities and infrastructure in Madrasah Aliyah Negeri 1 Ponorogo and to determine the relevance of facilities and infrastructure management to existing Islamic values. This study uses a field research method with a qualitative descriptive analysis approach. The results of this study indicate that the activities of educational facilities and infrastructure at Madrasah Aliyah Negeri 1 Ponorogo which include, planning and procurement, inventory, storage, maintenance, and elimination and destruction are in accordance with sura al-Hasyr verse 18 about the importance of thinking about the future, Al-Baqarah paragraph 282 is in accordance with inventory activities which explain about recording activities in muamalah, Al-Maidah paragraph 32 about the importance of maintaining goods, and Al-Israa verses 26-27 concerning storage and deletion of goods.